Neutrosophic cognitive map for the analysis of substances subject to control - Bryan Joel Morales Sánchez; Cristian Fernando Benavides Salazar; Julio Cesar Benavides Salazar; Erika Estefanía Barreiro Cedeño; Erika Estefanía Barreiro Cedeño (Neutrosophic Sets and Systems)
This study addresses the central problem of analyzing the commercialization of controlled substances using a neutrosophic cognitive map approach, a tool that has been little explored in this context. The need to investigate this phenomenon lies in the increasing complexity and ambiguity of controlled substances markets, where factors such as regulation, consumer behavior, government policies, and the evolution of supply and demand, generate a highly uncertain and dynamic environment. Despite previous research in the field of commercialization of these substances, traditional approaches fail to capture the interaction and combined effects of the multiple elements that influence the market. This study fills that gap by integrating the concept of neutrosophic to more accurately represent the relationships between these factors, taking into account the inherent imprecision in data and human behavior. The methodology used in this work is based on the construction of a neutrosophic cognitive map, which not only organizes and visualizes the interactions between the different elements of the commercialization process but also allows for modeling the uncertainty and nonlinear interactions between them. The results reveal that this approach offers a richer and more dynamic understanding of the controlled substances market, highlighting the key factors that contribute to fluctuating supply and demand and providing a useful tool for formulating more effective policies. The contribution of the study is significant, as it not only offers a new theoretical perspective on the analysis of complex markets but also provides a methodology that can be applied to other fields facing problems of uncertainty, such as the regulation of other controlled products or decision-making in highly complex contexts.